Da'wah Strategies of Islamic Boarding School Caregivers in Fostering Noble Character among Orphaned, Underprivileged, and Sabilillah Students at Nun Islamic Boarding School, Kudus - Mualamatul Musawamah; Wiwik Wijayanti (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study is motivated by the social conditions of orphans, underprivileged children (dhuafa), and beneficiaries of sabilillah, whose circumstances often place them in situations of economic, psychological, social, and educational disadvantage. Nun Islamic Boarding School (Pesantren Nun) serves as an institution that accommodates children from these backgrounds by providing free living facilities and education. The boarding school aims to cultivate akhlakul karimah (noble character) among its students, enabling them to develop moral integrity, independence, and resilience in facing life’s challenges. This research employs a descriptive qualitative approach. Data were collected through (1) observation, (2) interviews, and (3) documentation. The data analysis process consisted of (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusion drawing. The findings reveal that: (1) Pesantren Nun implements several strategies to foster akhlakul karimah among orphaned, underprivileged, and sabilillah students, including sentimental da’wah strategies (tazkiyatun nafs), rational da’wah strategies (tarbiyah dzatiyah), and sensory da’wah strategies (halaqah tarbawiyah). These approaches integrate spiritual, moral, and social dimensions to help students develop positive character and behavior. (2) The challenges encountered include student-related factors such as psychological conditions, the influence of advanced technology, inadequate parental attention, difficulties in student supervision, and diverse individual characteristics. Management-related challenges include the limited number of caregivers and their insufficient understanding of student development and guidance.